2021
DOI: 10.1016/j.psj.2020.09.090
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress alters muscle protein and amino acid metabolism and accelerates liver gluconeogenesis for energy supply in broilers

Abstract: Heat stress impairs growth performance and alters body protein and amino acid metabolism. This study was investigated to explore how body protein and amino acid metabolism changed under heat stress ( HS ) and the stress adaptation mechanism. A total of 144 broilers (28 d old) were divided into 3 treatment groups for 1 wk: HS group (32°C), normal control group (22°C), and pair-feeding group (22°C). We found that HS elevated the feed-to-gain ratio, reduced the ADFI and ADG, decreased breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 57 publications
12
72
0
Order By: Relevance
“…This indicates changes in the glucose metabolism of the D-Met group after exposure to acute heat stress. Similarly, in consistent with our study, Ma et al [36] reported that the expression of PCKc (PCK-cytosolic form) and PCKm (PCK-mitochondrial form) was significantly increased in the broiler group exposed to heat stress.…”
Section: Plos Onesupporting
confidence: 93%
“…This indicates changes in the glucose metabolism of the D-Met group after exposure to acute heat stress. Similarly, in consistent with our study, Ma et al [36] reported that the expression of PCKc (PCK-cytosolic form) and PCKm (PCK-mitochondrial form) was significantly increased in the broiler group exposed to heat stress.…”
Section: Plos Onesupporting
confidence: 93%
“…It was found that protein synthesis and N deposition were depressed and proteolysis increased during HS [34]. AA catabolism was enhanced under chronic HS [13]; thus, all plasma free AA concentrations decreased, except for glutamic acid, aspartic acid, and phenylalanine. Based on these studies, protein breakdown may increase rapidly in very short-term HS, resulting in a decrease in protein synthesis and an increase in plasma uric acid levels, but then decrease protein breakdown and maintain uric acid levels around normal concentrations as the thermal stress continues.…”
Section: Effect Of Hs On Protein Metabolism or Turnovermentioning
confidence: 99%
“…The metabolic fate of absorbed AA mainly depends on nutrient availability [17]. AA moving through catabolic pathways ultimately serve as precursors of gluconeogenesis [13] and contribute to 40% of the total AA loss in fasted animals. Proteins are synthesized from free AA, which become available either from dietary (the end product of digestion) or from metabolic origins as the result of AA biosynthesis within the body.…”
Section: Amino Acid And/or Protein Metabolismmentioning
confidence: 99%
See 2 more Smart Citations